Simplifying High-Density Memory: Exploiting Self-Rectifying Resistive Memory with TiO2/HfO2 Bilayer Devices - Min Gyoo Cho; Jae Hee Go; Byung Joon Choi (Archives of Metallurgy and Materials, 2024)
Self-rectifying resistive memory can reduce the complexity of crossbar array architecture for high density memory. It can replace integrated memory and selector with one self-rectifying cell. Such a simple structure can be applied for the vertical resistive memory. Both top and bottom interface between insulating layer and electrodes are crucial to achieve highly self-rectifying memory cell. In this study, bilayer devices composed of HfO2 and TiO2 were fabricated using atomic layer deposition (ALD) for the implementation of self-rectifying memory cells. The physical, chemical, and electrical properties of HfO2/TiO2 and TiO2/HfO2 sandwiched between Pt and TiN electrodes were investigated. By analyzing the conduction mechanism of bilayer devices, the higher rectification ratio of TiO2/HfO2 stack was due to the difference in height and the number of energy barriers.